Methodical instructions to perform the control work in the discipline "Аnalytical tools for financial and economic security" - Yurieva, Iryna; Tkachenko, M. O. (National Technical University "Kharkiv Polytechnic Institute", 2024)
Objective of the discipline: study of methodological approaches to solving the problem of implementing tools for financial and economic security of enterprises, mastering the knowledge and skills necessary for: - analysis and diagnostics of the financial and economic condition of the enterprise; - development of skills to identify violations of financial, banking, budgetary, tax, insurance, personnel, and other components of the discipline, to analyse and establish the causes of their occurrence and ways to overcome them; - development of skills to properly carry out measures and use means, monitor the implementation of proposals to eliminate identified shortcomings, violations and threats to the economic security of the enterprise; - identification and assessment of threats to the economic security of the enterprise; - development and implementation of measures to protect the financial and economic security of the enterprise. Formation of competences that allow: to use modern methods and tools for analysing financial and economic security; to make informed management decisions to protect the economic security of the enterprise; to effectively counteract internal and external threats to the financial and economic security of the enterprise. Study of the following topics: theoretical foundations of financial and economic security; methodology for analysing the financial and economic state of an enterprise; system of indicators of financial and economic security; methods of diagnosing and assessing threats to the financial and economic security of an enterprise; development and implementation of a system for protecting the economic security of an enterprise; monitoring and control of the financial and economic security of an enterprise.
Keywords: methodical instructions; economic security; finance; management; budget; banking